Perception of Interventional Radiology among Jazan Medical Students: Assessment of Knowledge and Career Intentions - Bahkali, Salha Al; Harbi, Ali Al; Kamili, Fatimah; Rashidi, Ibrahim Al (The Arab Journal of Interventional Radiology, 2021)
Context Lack of awareness among the students in the medical field is the greatest challenge to overcome in the emergence of contemporary interventional radiology (IR).Objectives We aimed to conduct a survey among medical students of Jazan University to explore their knowledge about IR, interest in IR as a future career, and preferred methods of training in IR.Materials and Methods This was a cross-sectional, self-directed questionnaire study. The target population was all medical students at Jazan University. Surveys were sent to 600 students. The questionnaire consisted of 11 closed and open-ended questions.Statistical Analysis We calculated the size of the sample using the Raosoft Sample Size Calculator Web site. Data analysis was performed using SPSS statistics.Results A total of 270 students responded (45%); more than half of the respondents (58.5%) were in the preclinical stage, while the rest were in the clinical stage. About 62.5% of clinical students and 66.4% preclinical students reported that their perception regarding the terminology of IR was good or excellent. Regarding the identification of interventional radiologists, 50.9% from the clinical students thought them to be radiologists and 50% from preclinical students also identified them as such.About 29.5% from the clinical students and 27.8% from the preclinical students thought them special surgeons, and 31.3% clinical students compared with 30.4% preclinical students believed they are vascular surgeons working with X-rays. About 19.6% clinical students compared with 17.7% preclinical students said they are general surgeons working with X-rays, and 48.2% clinical students compared with 45.6% preclinical students said they are special radiologists who work with percutaneous techniques. There was a significant difference (p = 0.041) in the responses between preclinical and clinical students regarding knowledge about what this medical specialty does. About 60.8% of clinical students reported that their knowledge and information regarding IR are efficient in comparison to 39.2% of preclinical students.Conclusion This study demonstrated that the basic knowledge among Jazan medical students is poor. About half of the respondents were clinical students who understood the radiology specialty, compared with one-third of preclinical students. This could impact the student’s decision toward IR as a future career.
Keywords: awareness; interventional radiology; medical students; Jazan